PENANGGULANGAN TINDAK PIDANA PERKOSAAN TERHADAP ANAK DI BAWAH UMUR ( STUDI KASUS DI POLRES TABANAN ) - Bambang Anom Partha Beda Awa; I Made Tjatrayasa; A.A. Ngurah Yusa Darmadi (Kertha Negara : Journal Ilmu Hukum, 2013)
Regarding the issue of the children, they often get the wrong treatment, especiallythe problem of sexual crimes. Children are often victims of sexual crimes in particularrape committed by adults and who are victims are minors. Therefore, this paper willdescribe the efforts of crime prevention rape of minors and contributing factor in theregional police of Tabanan . Based on the research directly in Tabanan district police,high children’s rape case that occurred in the region of Tabanan is police in because ofmany factors whicht cause crime of rape, these the were factors less parentalsupervision, alcohol factor and up to a factor vcd porn adult dating , so that the manyfactors rape of children especially in Tabanan is police then there must also be tackledin order to create safety in the community, especially in children. countermeasures beundertaken by the police was to provide socialization Tabanan’s police to schools,eradicating alcohol and porn vcd to improve security in the district police of tabanan.